PENGGUNAAN KODE TERBATAS PADA MASYARAKAT TUTUR BAHASA INDONESIA DI JAWA TENGAH - Hari Bakti Mardikantoro (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2006)
Use of Ianguage cannot be discharged from social and situasional factors. Social and situasional factors influencing usage of language cause language variation of appearance. Language variation can be differentiated into two kinds namely is elaborated code variation and restricted code variation. This research uses limited data. As source of its data language by speech community in Central Java is used. The data are collected by using obsevation method with simak libat cakap (SLC) technique and simak bebas libat cakap (SBLC) technique. Data analysis is carried out using descriptive qualitative method. Restricted code of Indonesian community in Central Java has some variations i.e., fonological variation, morphological, lexicon, and syntax. Restricted code variation is due to factors such as habit of language use, thinking process, Javanese influence, and dialectal influence.